A comprehensive assessment of eurocode 3 pt. 1.1 & NBR 8800 steel design codes. (13th September 2017) - da S. Vellasco, Pedro C. G.; de Lima, Luciano R. O.; da Silva, Luís Simões; Simões, Rui; Gervásio, Helena
ABSTRACT: This paper compares the axial force and bending moment design procedures of Eurocode 3 part 1.1 and the Brazilian Standard NBR8800. This comparison was performed through a series of practical design examples that were executed according to EC3 pt. 1.1 [1] and NBR 8800 [2]. This strategy led to an assessment of some critical design issues present in these two structural steel codes, focusing on the identification of their main similarities and differences. The main conclusions of the above‐mentioned comparisons will be presented in terms of steel profile axial force and bending moment design capacities. The main reason for this result presentation strategy was due to the fact that the most common steel profile tables are constructed in a discontinuous form, where the same steel profile is able to withstand a non‐negligible range of structural design capacities.